2011
DOI: 10.1017/s000711451000574x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 4-week very-high-fructose/glucose diets on insulin sensitivity, visceral fat and intrahepatic lipids: an exploratory trial

Abstract: An increasing amount of fructose in the diet is suggested to play a causal role in the pathogenesis of the metabolic syndrome, type 2 diabetes and fatty liver. Our aim was to investigate and compare the effects of very high fructose and very high glucose in hyperenergetic diets on glucose and lipid metabolism and on fat depots in healthy humans. We conducted an exploratory, prospective, randomised, singleblinded, intervention trial. Participants in addition to a balanced weight-maintaining diet received 150 g … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
152
5
9

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(170 citation statements)
references
References 32 publications
4
152
5
9
Order By: Relevance
“…In a recent study, overweight individuals randomized to drink sucrose-sweetened soda over 6 months had significant increases in intra-abdominal fat, but not total fat mass, relative to those in the isoenergetic milk condition (54) . In contrast, among healthy adults (BMI = 20-35 kg/m 2 ) participating in a 4-week weight maintenance feeding study of a diet supplemented with fructose or glucose 150 g/d (approximately 21 % of daily energy expenditure), Silbernagel et al (55) found no significant differences in changes in weight (kg), total body fat (kg) and visceral fat (kg) between diets. Additional research is needed to establish a definitive role of fructose in central fat accumulation (56) .…”
Section: Discussionmentioning
confidence: 95%
“…In a recent study, overweight individuals randomized to drink sucrose-sweetened soda over 6 months had significant increases in intra-abdominal fat, but not total fat mass, relative to those in the isoenergetic milk condition (54) . In contrast, among healthy adults (BMI = 20-35 kg/m 2 ) participating in a 4-week weight maintenance feeding study of a diet supplemented with fructose or glucose 150 g/d (approximately 21 % of daily energy expenditure), Silbernagel et al (55) found no significant differences in changes in weight (kg), total body fat (kg) and visceral fat (kg) between diets. Additional research is needed to establish a definitive role of fructose in central fat accumulation (56) .…”
Section: Discussionmentioning
confidence: 95%
“…This has coincided with a furore over the link between sugar and health, and the adverse outcomes of short-term, mechanistic studies that intervened with excessive amounts of fructose or sucrose (>20 % total energy) from sugarsweetened beverages (27)(28)(29)(30)(31) . Reassuringly, the outcome of these studies have not been reproduced in interventions with moderate intakes of fructose or sucrose, especially under iso-energetic conditions, and are thus unlikely to translate to the effects produced by habitual intakes of sugar.…”
Section: Influence Of Dietary Sugar (Sucrose and Fructose) On Lipid Mmentioning
confidence: 99%
“…The remaining 16 reports were reviewed in full. A total of 11 reports were selected for analysis, providing data for 15 trials: 13 isocaloric 14,15,17,27,28,[32][33][34][35][36] and 2 hypercaloric feeding trials, 27,37 with a median follow-up of 4.0 weeks (range: 15.5 days to 10 weeks).…”
Section: Statistical Analysesmentioning
confidence: 99%